The emergence and spatial distribution of Chinese seaport cities - Michael Funke; Hao Yu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
Seaports have historically played a key role in facilitating trade and growth. This paper is the first attempt in the literature to analyse the formation of Chinese seaport cities and the dynamics that drives it. First, we aim to identify theoretically the emergence of urbanized seaports with the help of a formal economic geography model. Second, employing an empirically plausible parameterisation of the model, we calibrate the evolutionary process and spatial distribution of seaports along the Chinese coastline.
URN:NBN:fi:bof-201408072012
Keywords: 330